ANALISIS KEBIJAKAN AGENDA RISET NASIONAL PTKI 2025–2029 DALAM PENGEMBANGAN PENDIDIKAN TINGGI KEAGAMAAN ISLAM DI INDONESIA - Baenuri; Oki Setiana Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the National Research Agenda Policy of Islamic Higher Education Institutions (PTKI) for the period 2025–2029 as a strategic direction for the development of Islamic higher education in Indonesia. The PTKI National Research Agenda serves as a strategic instrument established by the Ministry of Religious Affairs to strengthen the quality of research, community service, and the academic contributions of PTKI in addressing various social, religious, educational, economic, and technological challenges. This study employed a qualitative approach using a document study method. Data were collected through the analysis of regulations, guidelines, and official documents issued by the Ministry of Religious Affairs of the Republic of Indonesia concerning the PTKI National Research Agenda 2025–2029. The data were analyzed using content analysis techniques to identify policy directions, research priority areas, and their implications for the development of Islamic higher education. The findings reveal that the PTKI National Research Agenda 2025–2029 is designed to strengthen an innovative, collaborative, and problem-solving-oriented research ecosystem. Research priorities include Islamic studies, religious moderation, digital transformation, sustainable development, Islamic economics, Islamic education, and community development based on Islamic values. The implementation of this policy has the potential to enhance the quality of the tri dharma of higher education, strengthen the academic competitiveness of PTKI, and promote the contribution of Islamic higher education to national development. Therefore, synergy among the government, higher education institutions, researchers, and other stakeholders is essential for the successful implementation of the PTKI National Research Agenda 2025–2029.